Anaesthetic Management of a Labrador Retriever Undergoing Adrenalectomy for Phaeochromocytoma Excision, a Case Report - Maidanskaia, Ekaterina Gámez; Spadavecchia, Claudia; Vincenti, Simona; Mirra, Alessandro (Frontiers in Veterinary Science, 2022)
1. Abstract Perioperative management of cases undergoing phaeochromocytoma removal should aim at normalizing blood pressure and heart rate, restoring volume depletion, and preventing catecholamine release induced by surgical manipulation. In this case report, a novel pharmacological approach in a dog undergoing surgical tumour excision is described. A 7-year-old 25-kg spayed female Labrador Retriever presented for repeated episodes of generalized weakness, pale mucous membranes, tachycardia, tremor, panting, vomiting and hypertension over the last month was referred for surgical treatment of a left-sided adrenal tumour with invasion of the caudal vena cava. Severe hypertensive episodes occurred repeatedly, starting early during the anaesthetic period, while clipping and cleaning the abdominal area, and continued intraoperatively when the tumour was handled. Moderate hypotension occurred once the tumour was isolated and worsened during temporary caudal vena cava flow interruption and cavotomy. The patient was treated preoperatively with phenoxybenzamine to prevent hypertensive crises. Intraoperatively, magnesium sulphate and urapidil were used to control blood pressure. This treatment was effective in reducing the magnitude of blood pressure spikes but not sufficient to prevent hypertensive peaks, especially during tumour manipulation. Hypotension was treated with synthetic colloid and crystalloid boli, and noradrenaline continuous infusion. Blood transfusion was performed in response to acute bleeding during cavotomy. The dog recovered successfully from anaesthesia and its quality of life was deemed excellent by the owner at the last follow up, 22 months after surgery. The histopathology confirmed the diagnosis of phaeochromocytoma with an invasion of the phrenicoabdominal vein. In the present case, we obtained a successful outcome but failed to provide haemodynamic stability throughout the procedure.